2011
DOI: 10.1002/macp.201100097
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of Polythiophene‐graft‐poly(methyl methacrylate) brushes with Poly(vinylidene fluoride): Morphology, Optical and Conductivity Properties

Abstract: Polythiophene‐graft‐poly(methyl methacrylate) brushes are synthesized by ATRP. They form miscible blends with poly(vinylidene fluoride) (PVDF) due to specific interactions between the >CO groups of PT‐g‐PMMA with the >CF2 groups of PVDF. PT‐g‐PMMA remains in the interlamellar, interfibrillar and interspherulitic regions of the PVDF crystals at both laterally and longitudinally aggregated states. In the blends both PVDF and PT‐g‐PMMA brushes have nanometer sizes, producing nanostructured polymer blends. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The melting ( T m ) and crystallization ( T c ) temperatures were taken as the peak temperature and the glass-transition temperature ( T g ) was recorded as the inflection point of the heat-capacity jump from the second heating curve. The crystallinity of the samples was calculated from the enthalpy of fusion obtained from the thermogram by dividing with the enthalpy of fusion of perfect PVDF crystal (104 J/g) . The thermogravimetric analysis (TGA) experiment was performed using a TA Instrument (model SDT Q 600) under a nitrogen atmosphere at a heating rate of 10 °C/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The melting ( T m ) and crystallization ( T c ) temperatures were taken as the peak temperature and the glass-transition temperature ( T g ) was recorded as the inflection point of the heat-capacity jump from the second heating curve. The crystallinity of the samples was calculated from the enthalpy of fusion obtained from the thermogram by dividing with the enthalpy of fusion of perfect PVDF crystal (104 J/g) . The thermogravimetric analysis (TGA) experiment was performed using a TA Instrument (model SDT Q 600) under a nitrogen atmosphere at a heating rate of 10 °C/min.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(vinylidene fluoride) (PVDF) is a semicrystalline electroactive polymer and is technologically important because of its piezo and pyroelectric properties. , It has a wide range of applications in supercapacitors, actuators, batteries, membranes, and in different optoelectronic devices. , It has five different crystalline polymorphs (α, β, γ, δ, ε,), and β-polymorph is the most important for its piezo and pyroelectric properties. , Recently, PVDF composites with different nanomaterials (e.g., clay, metal nanoparticles, CNTs, and graphene) have demonstrated the formation of a piezoelectric β-polymorph with a highly improved mechanical and electrical properties. So, nanocomposites of PVDF and modified CNTs are gaining importance for the development of new functional materials. …”
Section: Introductionmentioning
confidence: 99%
“…This technique was used to tune the electronic and optoelectronic properties of PTh‐ g ‐PMMA by blending with the commodity polymer, poly(vinylidene fluoride) (PVDF). Miscibility was achieved due to specific interactions between the PTh‐ g ‐PMMA C=O groups and the PVDF CF 2 groups, and the blend showed a slight blue shift in both the absorbance and photoluminescence spectra relative to the unblended graft copolymer …”
Section: Applications Of Functional Cp‐based Graft Copolymersmentioning
confidence: 99%
“…Atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain transfer (RAFT) polymerization have commonly been used to produce tailored surfaces with polymer brushes . Polymer brushes based on conductive polymers have been primarily described in the literature as a means to improve or alter properties of the backbone CP, including morphology, optical or mechanical properties, and solubility. Some CP-based brushes have also been explored as stimuli-responsive surfaces. , Grande et al reported the first study on grafting of brushes from an electrochemically produced backbone; however, no switching of the surface states was attempted. We recently reported electrochemical switching of the morphology of a poly(terthiophene)- graft -(polystyrene- b -poly(acrylic acid)) and ion-concentration-dependent switching of poly(pyrrole)- graft -poly(zwitterion) brush conformation, both of which were driven by the polymer redox process.…”
Section: Introductionmentioning
confidence: 99%